Ending legalised violence against children : all Africa special report - a contribution to the UN Secretary General's study on violence against children (Global Initiative to End All Corporal Punishment of Children LondonGB, 2006)
Reviews law and policy in relation to corporal punishment and deliberate humiliation of children in each state across Africa.
Keywords: CHILD ABUSE